DZIKIR DAN FIKIR SEBAGAI KONSEP PENDIDIKAN KARAKTER: TELAAH PEMIKIRAN KH. MUNAWWAR KHOLIL AL-JAWI - Muhammad Anas Ma`arif; Muhammad Husnur Rofiq (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2019)
This research is motivated the dimension of dhikr which is oriented to form a clean heart, the dimension of thinking forms a human with high intellectual (perfect reason). The implications of the integration of dhikr and thought will form an integral concept of education without dichotomy. From the moral knowing, moral feeling and moral action components which are combined with tazkiyatun nafs, it is expected that students can practice the values ​​embodied in the goals of character education. Purpose of this study aims to describe and analyze the dhikr and fikir according to KH Munawwar Kholil Gresik in the book of Faidhul Illah and its implications with the character dedication. Design/methodology/approach-of this research uses library research from the data of books that have been collected relevant to the theme.The results shows that he integration of dhikr and fikir as the concept of non-dichotomic character education. Dzikir continuously and systematically thinking will bring out the character of the learner is integral. Originality/value-Dhikr (tazkiyatun nafs) and fikir (knowledge) form the whole human character (ulul albab) as the concept of integralistic character education. Character is not only in form through cognitive learning but also necessary habituation of religious activities. When the dimension of dhikr which is oriented to form a clean heart, the dimension of thinking forms a human with high intellectual (perfect reason). The implications of the integration of dhikr and thought will form an integral concept of education without dichotomy. From the moral knowing, moral feeling and moral action components which are combined with tazkiyatun nafs, it is expected that students can practice the values ​​embodied in the goals of character education.